Development of a novel model for energy exchanger recovery system in buildings - Phua, Zai Yao (2017)
Environmental sustainability is a key topic in today’s context. Energy resources are scarce due to the finite fossil fuels available. Heating, Ventilation and Air Conditioning (HVAC) system requires huge amount of cost to operate and is essential to reduce massive cooling load. Energy Recovery Ventilator (ERV) is an equipment which uses the principle of regeneration through heat and mass transfer. It is able to recover some of the cooling load through offsetting the cooling load purely by the HVAC and with the use of the ERV. Many research had been done on the ERV using FLUENT but only utilized it for heat transfer problem due to some limitations in the module for solving mass transfer problem. The purpose of this project is to use the Computational Fluid Dynamics (CFD) software, particularly FLUENT, to investigate the performance of the quasi-flow type ERV. It further extends to the investigating and analysing on the effect of the parameters such as balanced flow, unbalanced flow, outdoor temperature variations, outdoor humidity variations, materials with different through-plane permeability and air channel pitch. In addition, the amount of electrical power savings is calculated and analysed. The two designs evaluated in this study are mainly the current experimental ERV without ribs and with 8 ribs. Both ERV designs show similar trend in both balanced and unbalanced flow except that the ERV with 8 ribs shows a better performance and lower performance in terms of sensible effectiveness and latent effectiveness respectively. For balanced flow at low velocity, both the effectiveness are at the maximum. For unbalanced flow, as the mismatch increases, the effectiveness decreases. The ERV without ribs saves a higher amount of electrical power compared to the ERV with 8 ribs. The best combination on savings for both designs occurs at high balanced flow velocity condition and the next best combination occurs when the supply air velocity is higher than the exhaust air velocity while keeping the velocity mismatch to a minimal. The trade-off for the ERV with 8 ribs is the higher fan power consumption at high velocity which is caused by the exponential increment in the pressure drop that would reduce the amount of savings. For low permeability material, ERV with 8 ribs is able to recover a higher amount of savings as compared to the ERV without ribs.